Sigma-Z-source inverters - Soon, Jing Jun (2015)
To increase the boost capability with minimum passive components, existing transformer-based Z-source inverter (ZSI) topologies require the turn ratio to be increased. This results in larger transformer windings to be used in high dc-ac voltage gain applications. This shortcoming is addressed in this study by introducing a sigma-ZSI (ΣZSI) that improves the dc-ac voltage gain by reducing the turn ratio leading to a lower winding transformer. The proposed topology is compared with the TZSI as they used the same number of transformers and capacitors configured in an X-shaped network. The comparison shows that the ΣZSI will have a higher dc-ac voltage gain at a turn ratio lower than 1.618 for a given shoot-through duty cycle allowing the use of smaller transformers. Simulation and experimental results have validated the effectiveness of the proposed ΣZSI.